Inversion Method for Calculating lll Conditioning in Dynamic Light Scattering (DLS) System: Application to Polydisperse Silica Suspension - Riszekiya, Egis; Liu, Kin Men; Setianto, Setianto; Faizal, Ferry (Universitas Padjadjaran, 2026)
This study presents the development and evaluation of a self-constructed Dynamic Light Scattering system using a digital oscilloscope as its main acquisition platform. The aim of this research is to investigate the ability of the oscilloscope-based approach to measure particle size distributions and to compare its performance with that of a conventional Dynamic Light Scattering instrument. Autocorrelation data collected at different temporal acquisition settings were processed using Tikhonov regularization, and the optimal regularization parameter was determined through analysis of the characteristic L-shaped curve. The results show that the temporal resolution of the oscilloscope strongly influences the stability and accuracy of the reconstructed particle size distributions. Measurements obtained at medium acquisition intervals provide the best agreement with the commercial system, producing sharp and well-defined particle size peaks. In contrast, excessively short or long acquisition windows introduce noise or loss of temporal detail, which affects the inversion results. Overall, the findings demonstrate that an oscilloscope-based Dynamic Light Scattering approach can serve as an effective and low-cost alternative for particle size characterization and has strong potential for future development into a portable and affordable optical measurement system.